Improve survival from prolonged mechanical ventilation: beginning with first step - Pan, Chun; Qiu, Haibo (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Although conventional invasive mechanical ventilation is a life-saving procedure for critically ill patients, it is the most important risk factor for ventilator-associated events (VAEs) (1-3). Patients with VAEs often need prolonged mechanical ventilation (PMV), which leads to increased family and financial burden (1) and worse prognosis (2). However, long-term outcomes associated with PMV are not fully understood (3). A recent meta-analysis reporting long-term survival of critically ill patients treated with PMV further highlights the worse prognosis posed by the patients (3). Pooled mortality associated with PMV at hospital discharge, 1 year, and beyond 1 year was 29% (95% CI: 26-32), 62% (95% CI: 57-67), and 66% (95% CI: 61-70), respectively. Moreover, only 19% [16-24] were discharged to home and only 50% [47-53] were successfully liberated from mechanical ventilation (MV). These results alarm the physicians that PMV increases not intensive care unit (ICU) and hospital mortality, but long-term mortality. Considering the worse short-term and long-term outcomes of PMV, timely and effective weaning from PMV is an important priority in primary care for critically ill patients. However, difficult or prolonged weaning is common and effective management weaning remains unclear. If physicians and intensivists focus on the problems, a first step to improve the outcomes of patients with PMV is reducing the incidence of PMV.